PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI (STUDI PADA KOMISI PEMILIHAN UMUM PROVINSI SULAWESI TENGGARA) - Yuyun Indrayani; Endro Sukotjo; La Ode Bahana Adam (Pascasarjana Universitas Halu Oleo, 2021)
This study aims to analyze the influence of organizational culture, motivation and discipline simultaneously on employee performance at the Southeast Sulawesi Provincial Election Commision.. Thisresearchwill beconducted at Electoral Commission Secretariat OfficeIn Southeast Sulawesi.This study uses HRM Theory and Organizational Behavior Theory as the basis for writing. The population in this study are all civil servans in the Electoral Commission Secretariat Office In Southeast Sulawesi consisting of 17 districts and cities, totaling 186 people. The sample in this study are 127 people with details of Southeast Sulawesi Province (21 people), Bombana Regency (7 people), North Buton Regency (7 people), North Kolaka Regency (7 people), South Konawe Regency (7 people), Muna Regency. (6 people), Bau-Bau Regency (7 people), Buton Regency (6 people), Kolaka Regency (7 people), Konawe Regency (7 people), North Konawe Regency (7 people), Wakatobi Regency (7 people), Kendari City (8 people), South Buton Regency (4 people), Konawe Islands Regency (4 people), East Kolaka Regency (8 people) and West Muna Regency (7 people).Therese archinstrument that will be used in the study are the Organizational Culture Questionnaire, the Motivation Questionnaire, the Discipline Questionnaire and the Employee Performance Questionnaire. The data will be analize by using inferential statistics, Multivariate Linear Regression, which is carried out with the help of SPSS 21. The results of this study indicate that 1) The results of the Organizational Culture hypothesis test have a positive and significant influence on employee performance. This can be seen from the regression coefficient of 0.212 with a p-value of 0.015. This positive relationship indicates that the better the organizational culture, the better the performance of employees at the Southeast Sulawesi Provincial Election Commision. 2) The results of the motivation hypothesis test have a positive and significant influence on employee performance. This can be seen from the regression coefficient of 0.384 with a p-value of 0.000. This positive relationship indicates that the better the motivation, the better the performance of employees at the Southeast Sulawesi Provincial Election Commision. 3) The results of hypothesis testing indicate that discipline has a positive and significant effect on employee performance. This can be seen from the regression coefficient of 0.393 with a p-value of 0.000. This positive relationship indicates that the better the employee discipline, the better the performance of employees at the Southeast Sulawesi Provincial Election Commision.